Burnout, liderazgo y satisfacción laboral en el personal asistencial de un hospital de tercer nivel en Bogotá (2013)
The aim of this study is identify the presence of burnout; leadership styles and job satisfaction of professionals in a third level hospital and see if these are related, considering sociodemographic variables. We used the Spanish version of MBI, the TAP and Job Satisfaction Test S20/23. According to the results, we found low presence of burnout and high levels of personal accomplishment, despite the adverse labor conditions, commonly precursors of the syndrome. Contrary to reported in the literature, people with the syndrome or significant risk, have high job satisfaction, based on intrinsic motivation, which constitute a protective factor. There was no direct relationship between leadership and burnout, but leadership is relates to job satisfaction through intrinsic motivation. The mediating role of sociodemographic variables is confirmed.Keywords: Burnout Syndrome, job satisfaction, leadership.